2009
DOI: 10.1186/1472-6823-9-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, predictive factors and outcome of hyperglycaemic emergencies in a developing country

Abstract: Background: Hyperglycaemic emergencies are common acute complications of diabetes mellitus (DM) but unfortunately, there is a dearth of published data on this entity from Nigeria. This study attempts to describe the clinical and laboratory scenario associated with this complication of DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
39
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 11 publications
12
39
10
Order By: Relevance
“…Nineteen subjects (18%) with hyperglycaemic emergency were presenting with diagnosis of DM for the first time. This finding is in keeping with the reports from the study done by Ehusani 17 , Ogbera et al 21 and Adesina 22 who reported prevalence rates (newly diagnosed DM) of 13.3%, 15% and 46% respectively. Another study done by Pepper et al 23 , in South Africa reported a prevalence of 11% 23 .…”
Section: Plasma Glucose At Presentationsupporting
confidence: 81%
See 2 more Smart Citations
“…Nineteen subjects (18%) with hyperglycaemic emergency were presenting with diagnosis of DM for the first time. This finding is in keeping with the reports from the study done by Ehusani 17 , Ogbera et al 21 and Adesina 22 who reported prevalence rates (newly diagnosed DM) of 13.3%, 15% and 46% respectively. Another study done by Pepper et al 23 , in South Africa reported a prevalence of 11% 23 .…”
Section: Plasma Glucose At Presentationsupporting
confidence: 81%
“…Diabetic ketoacidosis was found in 31% of patients and their mean (SEM) age was 43.4 (3.00) years. This finding is similar to the reports by Ehusani 27 , Ogbera et al 21 , Okoro et al 20 and Adesina 22 who, in their various studies noted the occurrence of DKA in older subjects. Nine (33.3%) of the patients with DKA were less than 30 years and this could be attributed the fact that majority of these persons had type 1 DM, which typically presents at a younger age (usually less than 30 years) 11 .…”
Section: Pattern Of Hyperglycaemic Emergenciessupporting
confidence: 81%
See 1 more Smart Citation
“…Otherwise, hypokalemia was the common abnormality (17.8%). Authors report this disorder in ketosis emergencies with a frequency ranged from 5.6% to 47% [2] [13] [14], and kalemia sometimes can collapse below 2 mmol/l [13]. Because low normal or normal kalemia during these emergencies result in an absolute depletion of potassium, the risk of iatrogenic hypokalemia prompt to delay the onset of intensive insulin therapy as long as potassium is below 3.3 mmol/l [4] [15].…”
Section: Discussionmentioning
confidence: 99%
“…A study from India, with 68 patients, showed that the most common complications during DKA treatment were hypokalemia in 41% of the cases, hypoglycemia in 15% of the cases, and cerebral edema in 13.2% of the cases (7). In another recent study, Ogbera and cols., evaluated 111 patients with hyperglycemic emergencies, and showed that hypokalemia occurred in 37% of the cases, being considered a predictor of death (8).…”
mentioning
confidence: 99%